THE EFFECT OF VIDEO COUNSELING ON PERSONAL HYGIENE KNOWLEDGE IN ADOLESCENT GIRLS - Widiastuti, Dhias; Octaviani, Dhita Aulia; Saputri, Meilina Intan Dewi (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
Personal hygiene is important for the health of adolescent girls. Video counseling is effective in improving hygiene knowledge, especially due to its easy access and good visualization. The research method used an experimental design with one group of adolescent girls aged 13-18 years from junior high school. Hygiene knowledge was measured before and after video counseling. The research results showed a significant increase in hygiene knowledge after the video intervention. This indicates the effectiveness of video counseling in raising awareness among adolescent girls about personal hygiene. In conclusion, video counseling is effective in enhancing hygiene knowledge among adolescent girls. Recommendations for health counseling include using engaging and effective video media.